The Functional Impact of Alternative Splicing and Single Nucleotide Polymorphisms in Rheumatoid Arthritis - Aravilli, R. K.; Vikram, S. Laveen; Kohila, V. (Current Pharmaceutical Biotechnology, 2021)
Advances in genomics and proteomics aid the identification of genes associated with various diseases. Genome-Wide Association Studies (GWAS) have identified multiple loci as risk alleles for susceptibility to Rheumatoid Arthritis (RA). A bisection of RA risk can be attributed to genetic factors. Over 100 associated genetic loci that encompass immune regulatory factors have been found to be linked with RA. Aberrant Single Nucleotide Polymorphisms (SNPs) and alternative splicing mechanisms in such loci induce RA. These aberrations are viewed as potential therapeutic targets due to their association with a multitude of diseases. This review presents a few imperious genes whose alterations can cause severe bone deformities culminating in RA.
Keywords: alternative splicing